LK-to-NK transformation - Koshimura, Miyuki (1989)
Abstract: "This paper describes LK-to-NK transformation which maps a proof in LK to a proof in NK. We prove that a cut-free proof in LK is mapped to a normal proof in NK, in a sense, by the transformation. This is used to develop user oriented explanation facilities in automatic theorem provers and proof checkers."
Keywords: Automatic theorem proving; Man-machine interaction